2022
DOI: 10.1080/0886022x.2022.2106872
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and risk factors of chronic kidney disease progression in patients with diabetic kidney disease and non-diabetic kidney disease: a prospective cohort CKD-ROUTE study

Abstract: Diabetic kidney disease (DKD) is emerging rapidly as the leading cause of chronic kidney disease (CKD) worldwide. In this 3-year prospective, multicenter cohort study, a total of 1138 pre-dialysis CKD patients were recruited. Patients were categorized into two groups according to the etiologies of DKD and non-diabetic kidney disease (NDKD). Propensity score matching was performed to adjust for confounding factors, resulting in 197 patients being assigned to DKD and NDKD groups, respectively. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…It is important to distinguish CKD subtypes, especially between DKD and non-diabetic kidney disease (NDKD) for disease prevention and clinical practice 15 16. A 3-year prospective, multicenter cohort study found that patients with DKD had a higher risk of a worse prognosis than NDKD (HR=2.30, 95% CI 1.48 to 3.58) 17. The present study is the first to explore the associations between DM and CKD subtypes and found that DM was associated with both DKD and NDKD (ie, glomerulonephritis) in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish CKD subtypes, especially between DKD and non-diabetic kidney disease (NDKD) for disease prevention and clinical practice 15 16. A 3-year prospective, multicenter cohort study found that patients with DKD had a higher risk of a worse prognosis than NDKD (HR=2.30, 95% CI 1.48 to 3.58) 17. The present study is the first to explore the associations between DM and CKD subtypes and found that DM was associated with both DKD and NDKD (ie, glomerulonephritis) in Chinese adults.…”
Section: Discussionmentioning
confidence: 99%
“…About 20%–40% of diabetes can progress to DN ( 1 ). It is a leading contributor of DN to kidney failure in developed countries ( 17 , 18 ). Therefore, early diagnosis and intervention in DN are particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is the most common cause of CKD worldwide. Compared to other causes of CKD, patients with CKD and diabetes are at a higher risk of developing end-stage renal disease (ESRD), which imposes a huge health and economic burden on both patients and society [17]. Hypertension is also a risk factor for CKD.…”
Section: Discussionmentioning
confidence: 99%